The accuracy of free-hand cup positioning: a CT based measurement in a South Indian hospital - Sengodan, Vetrivel Chezian; Marimuthu, S.; Ramasamy, Raghupathy (International Journal of Research in Orthopaedics, 2018)
Background: In total hip arthroplasty, the restoration of normal hip center in acetabular reconstruction encourages the normal bio mechanics. The impingement, dislocation, and implant wear have increased the interest in accurate component placement in arthroplasty. This study is to determine the accuracy of the free hand technique in the acetabular cup placement in relation to native acetabulam using CT scan images. Methods: This study was done in the Coimbatore Medical College and Hospital from June 2015 to March 2016. Twenty patients who have undergone total hip replacements were subjected to CT scan of pelvis preoperatively and postoperatively. The acetabular cup version and the inclination were measured and analyzed statistically. Results: The mean acetabular version was 17.5◦±6.5◦ and the inclination was 46.6◦±9.3◦ pre operatively. Post operatively the mean acetabular version was 26.3◦±17.3◦ and the inclination was 41.7◦±10.9◦. With reference to the component version it ranged from 12.5˚ of retroversion to 62.5˚ anteversion with a mean of 26.3◦±17.3◦. The component inclination ranged from 15.6◦ to 58.4◦ with a mean of 41.7◦±10.9◦. On combining component version and inclination, only (50%) was within the safe zone. Conclusions: Based on the CT finding acetabular version and inclination differs from individual to individual. During acetabular cup placement in total hip arthroplasty using free hand technique, our study shows that that inclination is better achieved and the anteversion is over targeted in most of the cases.